Impact of the German real estate transfer: Tax on the commercial real estate market - Coletta Frenzel Baudisch; Carolin Dresselhaus (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2018)
The tax burden of real estate transactions in Germany increased considerably since the constitutional reform in 2006. We examine the impact of the real estate transfer tax (RETT) on transactions and (net-of-tax) prices of commercial buildings and vacant commercial lots by means of a fixed-effects panel regression. The empirical analysis shows an association of a rise of the RETT by 1% with a decrease of office transactions by up to 0.41% and reduced prices by up to 0.22%. On the market for other commercial properties, transactions and prices decline by 0.17% and 0.19% respectively following a RETT increase. The negative price effects on the commercial real estate market tentatively indicate tax incidence with the seller. In the case of vacant commercial lots, a RETT increase seems to induce an increase of average prices by 0.36%, denoting tax incidence with the buyer. We find no significant effect on transactions of vacant lots in the data. In addition, we analyze possible neighborhood effects among the states. The empirical evidence for these effects implies that with an average of a 1% RETT increase in the bordering states of one state, the prices for other commercial properties and for vacant lots rise by 0.51% and 0.71% respectively. Hence, the border effect seems to surpass the direct price effect and suggests spatial structural changes in the investment behavior.
Keywords: H20; H22; H77; R33; 330; real estate transfer tax; commercial real estate market; share deal; panel regression